The mediating role of the ability to adapt to teleworking to increase the organizational performance - Mihail Busu; Attila Gyorgy (Amfiteatru Economic Journal, 2021)
In this article, the authors develop an econometric model to determine the impact of professional telework activities on the degree of employees' performance, based on the ability to adapt to the new labor system. The data were collected using a questionnaire addressed to employees of companies that provide financial consultancy in Romania and were analyzed using the statistical software Smart-Pls 3.3.2. Starting with the literature of profile, the paper identifies the drivers of the organizational performance model in carrying out professional activities in the remote working system. These indicators are independent variables that model the impact of telework activities on business performance. The results of the study confirm the hypotheses presented in the article, emphasizing that the performance indicator of employees working in the remote system is the direct and intrinsic result of the collaboration of several factors, such as personal psychological, economic, and professional needs, system variables and regulation, while the ability to adapt to telework has a moderator effect between independent variables and the organizational performance. Identifying the determinants that contribute to increasing organizational performance through professional activities in telework is relevant for the human resource management, to value the positive aspects, such as the ability to actively involve employees, rewarded for their work and to prevent their resilience to change.
Keywords: O12; M10; C30; C83; 330; telework; organizational performance; econometric model; Partial Least Squares (PLS); Structural Equation Modelling (SEM); ability to adapt; COVID-19; psychological impact